Pengaruh pemahaman perpajakan, tarif pajak, dan sanksi perpajakan terhadap kepatuhan wajib pajak - Intan Permata, Merry; Zahroh, Fatmawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Tax is a mandatory levy that is used as a source of state revenue that is used by the government to finance development and government spending. Tax revenue is the largest domestic revenue, where the greater the State expenditure in financing efforts, the State is required to increase the State revenue, the source of which is tax revenue. The study used a descriptive method utilizing a quantitative approach. Questionnaires were used as a method for collecting data for this research. Primary data is used as the type and source of research data. This study aims to examine the effect of understanding taxation, tax rates, tax sanctions on taxpayer compliance. The object of the research is MSME actors who are registered as members of the PLUT K-UMKM Batu City. The data collected were 95 samples. The technique of distributing data is by spreading the google form link to the respondents. Multiple linear regression analysis was determined to be a means to analyze the data. This study obtained the results that the understanding of taxation and tax sanctions have a positive and significant effect on taxpayer compliance, while tax rates do not have a positive effect on taxpayer compliance. And an understanding of taxation, tax rates and tax sanctions in a simultaneous manner against taxpayer compliance.